Indirect task instructions better reveal theory-of-mind impairment, independent of executive dysfunction, in schizophrenia. (October 2017) - Langdon, Robyn; Connors, Michael; Connaughton, Emily
Abstract: Theory of mind (TOM) impairments associate significantly with executive deficits in schizophrenia, consistent with the proposal that executive abilities can limit TOM task performance, and confounding identification of those patients who would benefit most from targeted mentalising interventions. 50 schizophrenia patients and 30 healthy controls completed an executive battery and four TOM tasks that were alike with regards generating overt measures of causal false-belief reasoning, but differed with regards using indirect (vs. more direct) instructions. Only the TOM tasks that used indirect instructions to elicit spontaneous false-belief inferences revealed impairment, independent of executive dysfunction, in the schizophrenia patients. Highlights: Theory of mind (TOM) and executive impairments co-occur in schizophrenia. Executive impairments can obscure the extent of underlying TOM impairment. Schizophrenia patients and controls completed a battery of executive and TOM tasks. TOM tasks varied with regards their use of more directed vs. indirect instructions. Only the latter distinguished between groups, controlling for executive measures.